2011
DOI: 10.1007/s00330-011-2305-1
|View full text |Cite
|
Sign up to set email alerts
|

One-to-one comparison between digital spot compression view and digital breast tomosynthesis

Abstract: • Digital spot compression views (DSCVs) are often needed in breast screening programmes. • Digital breast tomosynthesis (DBT) now offers an alternative to DSCV • In recalls without calcification, DBT was at least equally accurate as DSCVs • DBT has a lower mean glandular dose than DSCVs • Thus DBT has the potential to help reduce the recall rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 13 publications
2
61
1
1
Order By: Relevance
“…Although this study was not designed to assess DBT in the diagnostic and assessment setting, improved visualisation of benign and malignant features using DBT could reduce the need for additional ultrasound, MRI or supplemental mammographic imaging. [39][40][41][42] The screening population would also benefit if some of the anxiety and stress associated with breast screening from unnecessary recalls and additional testing could be reduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study was not designed to assess DBT in the diagnostic and assessment setting, improved visualisation of benign and malignant features using DBT could reduce the need for additional ultrasound, MRI or supplemental mammographic imaging. [39][40][41][42] The screening population would also benefit if some of the anxiety and stress associated with breast screening from unnecessary recalls and additional testing could be reduced.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] Improved lesion visibility, size and classification compared with standard film or digital mammography have been reported [31][32][33][34][35][36][37][38] and the possibility that DBT could reduce the need for additional mammographic views at least for non-calcified lesions [39][40][41][42] has been suggested. There are mixed reports of the sensitivity of DBT for the detection of microcalcifications 32,[43][44][45][46][47][48][49][50][51] that may be partly as a result of the different techniques used for image reconstruction and the need to combine image slices into thicker slabs for optimal visualisation of microcalcification clusters.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…[3][4][5] DBT has also been found to be superior to FFDM in measuring tumour size 15,16 and is at least comparable with supplementary views in the assessment of non-calcified lesions. [9][10][11] The tumour outline can be seen in more cases on DBT as compared with FFDM, which makes local staging of tumours significantly more accurate with DBT. 15 The combination of DBT and FFDM has also been found to increase cancer detection and reduce recall rates in females with dense breasts.…”
Section: Resultsmentioning
confidence: 99%
“…8 The focal compression is intended to spread out overlying glandular tissue and improve the conspicuity of any underlying lesion. Other studies 9,10 have confirmed that DBT is at least as accurate as spot compression view in the assessment of soft-tissue abnormalities. A study by Zuley et al 11 has shown that DBT significantly improved diagnostic accuracy and allows better lesion characterization for non-calcified lesions in comparison with supplemental mammographic views.…”
Section: Introductionmentioning
confidence: 85%
“…Early studies of DBT have shown improved conspicuity and characterization of lesions, in part due to reduced obscuration by overlapping breast tissue (15,25). In particular, architectural distortion and lesion margins become more apparent at DBT.…”
Section: True-positive Findings: Improved Cancer Detectionmentioning
confidence: 99%